Становлення археологічної школи на Буковині (до 100-річчя від дня народження Б.О. Тимощука) - Михайлина, Л.П.; Пивоваров, С.В. (Археологія, 2019)
Подається короткий біографічний нарис та творчий
шлях відомого українського археолога, історика, краєзнавця, популяризатора археологічних знань Б.О. Тимощука, якому виповнилося 100 років від дня народження
у квітні 2019 р. Исполнилось 100 лет со дня рождения известного украинского археолога, историка, краеведа, популяризатора
археологических знаний Бориса Анисимовича Тимощука (1919—2019). Большая часть жизни и научного творчества ученого связана с Буковиной и г. Черновцы. Свою научную деятельность он начал в конце 1940-х гг. в качестве археолога в местном областном краеведческом музее. В конце 1960-х г. перешел на работу в Черновицкий государственный университет, а в 1970 г. продолжил свою научно-исследовательскую деятельность в Черновицком
отделе Института истории АН Украины. В 1984—1997 гг. работал на должности ведущего научного сотрудника
Института археологии АН СССР (с 1992 г. — Института археологии РАН).
С именем Б.А. Тимощука связано открытие большинства археологических памятников Буковины. Особое место в его научной деятельности занимали исследования раннеславянских древностей пражско-корчакской и райковецкой культур, а также археологические памятники эпохи Киевской Руси и Галицко-Волынского княжества.
Археологические исследования Б.А. Тимощука продолжают его ученики и последователи. В Черновицком
национальном университете имени Юрия Федьковича проводятся научные конференции в честь Б.А. Тимощука.
На доме, где жил ученый, установлена мемориальная доска. Решением Черновицкого городского совета одна из
улиц города названа его именем. В 2018 г. Б.А. Тимощук награжден Почетным знаком отличия Черновицкого областного совета «За заслуги перед Буковиной» (посмертно). A famous Ukrainian archaeologist, historian, local historian and popularizer of archaeological knowledge Borys Onysymovych
Tymoshchuk would have turned 100 this year(1919-2019). Even more of hislife and scientific creative activitywas associated
with Bukovyna and Chernivtsi. He started his scientific activity in the late 1940-ies as an archaeologist in the local regional
museum.In the late 1960-ies, he started working at Chernivtsi State University and in 1970 continued his research activity in
the Chernivtsi Department of the Institute of History of the Academy of Sciences of Ukraine. During 1984-1997 he worked
as leading research associate at the Institute of Archaeology of the Academy of Sciences of the USSR (since 1992 - Institute
of Archaeology of the Russian Academy of Sciences).
The discovery of most of the archaeological monuments in Bukovina was associated with B.O. Tymoshchuk’s name. A
study of the early Slavonic antiquities of the Prague-Korchak and Luka-Rajky Cultures, aswell as archaeological monuments
of the epoch of Kyivan Rus and Galicia and Volyn Principality had a special place in his scientific activity.
B.O. Tymoshchuk’s students and followers continue archaeological studies, conducted by him. The Yuriy Fedkovych
Chernivtsi National University holds scientific conferences in memory of B. O. Tymoshchuk. A memorial plate marks
the house where the scientist used to live. By decision of the City Council one street in Chernivtsi has been named after
him. In 2018 the Chernivtsi Regional Council awarded B. O. Tymoshchuk with the honorable badge of merit of Bukovina
posthumously.